Study of competitive binding of amlodipine besylate and benazepril hydrochloride to bovine serum albumin and their displacement interaction at the binding site - Israt Jahan, Anna Akter, Irin Dewan, Md. Selim Reza, S. M. Ashraful Islam (Journal of Applied Pharmaceutical Science, 2017)
The present experiment shows how clinically two important drugs, amlodipine besylate (AB) and benazepril hydrochloride (BH), bind with serum protein and their mutual effect to displace each other from their binding sites. Binding chemistry of amlodipine besylate and benazepril hydrochloride to bovine serum albumin (BSA) was evaluated by equilibrium dialysis method at pH 7.4 and 37°C temperature. The binding of these two drugs have been characterized by two sets of association constant: high affinity constant (K1) and low affinity association (K2) constant. The non-linear curve of the scatchard plot suggested high affinity binding sites (K1 = 8.47x105 M-1, n1=1.9) and low affinity binding sites (K2 = 0.33 x105 M-1 , n2=11.7) for amlodipine besylate. On the other hand for benazepril hydrochloride high affinity constant (K1) was 14 x105 M-1 (n1 =1) and low affinity constant (K2) was 0.31 x105 M-1 (n2 = 16 ). Site specific probe displacement data showed that amlodipine besylate primarily binds to site – I (the warfarin sodium site), while the low affinity site of this drug is Site- II (diazepam site) on BSA. On the other hand, benazepril hydrochloride primarily binds to site – II (diazepam site) on BSA. The investigated drugs compete for different site (site-I amlodipine besylate and site-II – benazepril hydrochloride) and they do not displace each other from bovine serum albumin, hence concurrent administration of these two drugs will not alter the therapeutic efficacy of each other and co-administered of these two drugs can be effective as a combination therapy in the management of hypertension.
Keywords: Amlodipine Besylate, Benazepril Hydrochloride, Diazepam, Warfarin Sodium, Serum Albumin, Equilibrium Dialysis,Binding Chemistry.